2021
DOI: 10.1590/1982-2170-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

The Geoid and Quasigeoid of São Paulo State Using the Updated Gravimetric Data and the 2018 BVRF

Abstract: The combination of physical and geometric heights, required for geodetic purposes, uses Global Geopotential Models (GGMs), local geoid, or quasigeoid models. The geoid height and the height anomaly, provided by GGMs, are not accurate enough for most engineering applications. Considering the normal height system of Brazil and the physical concepts of the involved reference surfaces, a quasigeoid model is more appropriate than the current Brazilian geoid model MAPGEO2015. This paper shows the determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, T GGM values show significant differences between order and degree 100 and 200. Silva (2021) studied the RMS difference between height anomalies, obtained from the GPS determinations on the leveling network, and the GOCO06S geoidal height of 86 points located in São Paulo state. In the study was observed a difference of 20 cm approximately, between degrees 100 and 200.…”
Section: Disturbing Potential Differences Of the Numerical Integratio...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, T GGM values show significant differences between order and degree 100 and 200. Silva (2021) studied the RMS difference between height anomalies, obtained from the GPS determinations on the leveling network, and the GOCO06S geoidal height of 86 points located in São Paulo state. In the study was observed a difference of 20 cm approximately, between degrees 100 and 200.…”
Section: Disturbing Potential Differences Of the Numerical Integratio...mentioning
confidence: 99%
“…In this paper, a quasi-geoid model of São Paulo (Silva et al, 2021), which has the same database used in Hotine's methodologies, was used. The was computed using the GRAVSOFT package (Forsberg & Tscherning, 2008).…”
Section: Recovering Potential Gravity Values From Existing Quasi-geoi...mentioning
confidence: 99%
See 1 more Smart Citation